2021
DOI: 10.1038/s41541-021-00340-5
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated dengue viruses are genetically more diverse than their respective wild-type parents

Abstract: Dengue poses a significant burden of individual health, health systems and the economy in dengue endemic regions. As such, dengue vaccine development has been an active area of research. Previous studies selected attenuated vaccine candidates based on plaque size. However, these candidates led to mixed safety outcome in clinical trials, suggesting it is insufficiently informative as an indicator of dengue virus (DENV) attenuation. In this study, we examined the genome diversity of wild-type DENVs and their att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Moreover, while the conventional sample pooling strategy adopted to achieve sufficient starting materials for sequencing has proved fruitful in identifying common variants, it may obscure low-frequency variants due to the averaging effect of combining individuals. Despite that, advances in next generation sequencing capabilities, specifically the ability to call low frequency variants (Wilm et al, 2012;Bifani DENV quasispecies diversity key questions…”
Section: Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, while the conventional sample pooling strategy adopted to achieve sufficient starting materials for sequencing has proved fruitful in identifying common variants, it may obscure low-frequency variants due to the averaging effect of combining individuals. Despite that, advances in next generation sequencing capabilities, specifically the ability to call low frequency variants (Wilm et al, 2012;Bifani DENV quasispecies diversity key questions…”
Section: Future Directionsmentioning
confidence: 99%
“…Likewise, for DENV and other closely related arboviruses, an optimal level of diversity in a quasispecies is required to maintain viral fitness ( Vignuzzi et al., 2006 ; Beck et al., 2014 ; Rozen-Gagnon et al., 2014 ; Beck et al., 2018 ). Studies have demonstrated that strains that have a significantly elevated or reduced level of quasispecies diversity compared to wildtype tend to be less fit ( Vignuzzi et al., 2008 ; Bifani et al., 2021 ). In DENV, clinically-tested successful attenuated vaccine candidate strains harbored a greater level of quasispecies diversity than their virulent parental strains ( Bifani et al., 2021 ).…”
Section: Optimal Genome Diversity Level Required For Dengue Virus Fit...mentioning
confidence: 99%
See 2 more Smart Citations
“…DENV-2 PDK-53 was derived from the wild-type DENV-2 16681 virus strain through serial passage in primary dog kidney cells ( 45 ). The attenuated DENV2 PDK-53 virus exhibits distinct features that differ from its parental strain, such as temperature sensitivity, less effective replication, attenuated neurovirulence, and greater genetic diversity, which affected the fitness of DENV2 PDK-53 ( 46 ). These features are mainly attributed to 5’-NCR-57 C-to-T, NS1-53 Gly-to-Asp, and NS3-250 Glu-to-Val mutations ( 45 ).…”
Section: Tak-003 Dengue Vaccine Candidatementioning
confidence: 99%